Essays on international trade and Bayesian forecasting - Edwards, Dennis S (ProQuest Dissertations & Theses, 2002)
Economic theory is subject to continual analysis. While theories themselves are sometimes widely accepted, nuances of theory are persistently scrutinized. Researchers have not isolated this debate from a simply theoretic standpoint. Empirical methods in microeconomics also provide a forum for disagreement. This dissertation studies two topics of microeconomic theory that are constantly in debate: integration and cost function estimation. From the standpoint of theoretical integration models in international trade theory, the concept of foreign direct investment is studied in both a horizontal and vertical setting. With respect to horizontal integration, this dissertation modifies the Brander-Krugman reciprocal dumping model to evaluate the effects on production and profit in an international duopoly under settings of non-controlling interest and managerial control. Counterintuitive results abound with managerial control, in that the acquiring firm will increase its exports abroad, despite the presence of transportation costs. Additionally, a discussion of antitrust and nationalist considerations that drive integration decisions is presented. This presents an introduction to a branch of theoretical literature that has seen constant conjecture: vertical integration. Various models of vertical integration are discussed, with the Ordover, Saloner, and Salop model in the foreground. The vertical integration model in this dissertation uses internal transfer pricing to describe the effects of input sales between the downstream and upstream divisions of a merged firm. With price leadership in the input market, foreclosure of downstream firms will occur, and these firms move toward a collusive equilibrium in the absence of tacit collusion among the downstream competitors. The dissertation concludes with a discussion of a debate among empirical researchers concerning the estimation of cost functions. There has been considerable discussion regarding the imposition of regularity conditions on cost functions. These conditions are imposed on the translog, and it seen that forecasting results are improved as a result. This leads to an important conclusion: economic theory matters in empirical work. While the constant scrutiny of theory will never conclude, this dissertation attempts to improve upon existing integration theory, and uses widely accepted economic theory to improve the means in which cost functions are estimated in empirical research.